Monetary theory and practice - Hanson, John Lloyd (London : Macdonald and Evans, 1974)
The book has been thoroughly revised to take account of the many recent developments in both monetary theory and in banking practice. Changing in almost every aspect of the subject follow one another with increasing rapidity in the modern world, and to bring the book up to date an extensive revision has been necessary.
Includes index
usc 31/05/2017
Loans
Keywords: Money; International finance; Banks and banking